Noise and Vibration Control in the Built Environment - Jian Kang (MDPI - Multidisciplinary Digital Publishing Institute, 2017)
With global urbanization rapidly rising and the increasing need of high-quality built environments, the requirement of achieving improved sound quality, both for outdoor and indoor environments, has received a lot of attention. This Special Issue collection reflects the current state of the art, with 12 papers covering environmental acoustics; the influence of soundscapes on people's behavior; soundscape pleasantness estimation; tranquility; perceived quality of sonic environments; sound and vibration-related health complaints concerning tramways; and the disturbance of construction machines; as well as in building and room acoustics, including natural ventilation-enabling façade noise control devices; the effect of external shading devices; rating method of airborne sound insulation; water supply and drainage noise, and the effect of diffusive surfaces in auditoria. Some papers cover research on the engineering aspects of sound and vibration, such as sound propagation and noise control techniques, as well as perception aspects of sound, such as indoor acoustic comfort and environmental soundscapes. The book is prefaced by Prof. S Wu, entitled 'Sustainable Urban Sound Environment'.